Security in Asia Pacific the dynamics of alignment - Wilkins, Thomas S. 1973- (Boulder, Colorado Lynne Rienner Publishers, Inc., 2019)
"Both a new approach to understanding security dynamics in Asia Pacific and an examination of the dominant alignments in the region: the US alliance system, ASEAN, and the Shanghai Cooperation Organisation"-- Provided by publisher.
Preface -- Security alignment in Asia Pacific : a new approach -- Alliances (redux) -- The Trilateral Security Dialogue -- Security communities -- The ASEAN Security Community -- Strategic partnerships -- The Shanghai Cooperation Organisation -- Rethinking alignment.
Recommended by Reglleto Imbong
Includes bibliographical references (pages 199-240) and index.
Keywords: ASEAN; Shanghai Cooperation Organisation; Security, International -- Asia; Security, International -- Pacific Area; Regionalism -- Asia; Regionalism -- Pacific Area; Asia -- Foreign relations; Pacific Area -- Foreign relations